(untitled) (Clinics, 2014)
OBJECTIVE: To analyze the clinical results of a partial vertebrectomy with titanium mesh implantation and pedicle screw fixation using a posterior approach to reconstruct the spine in the treatment of thoracolumbar burst fractures. METHOD: From January 2006 to August 2008, 20 patients with severe thoracolumbar fractures were treated.For vertebral bodies associated with one injured intervertebral disk, subtotal vertebrectomy surgery and single-segment fusion were performed. For vertebral bodies with two injured adjacent intervertebral disks, partial vertebrectomy surgery and two-segment fusion were performed. RESULTS: All 20 patients were followed up for 12 to 24 months (average of 18 months). There were no complications such as wound infections, hemopneumothorax or abdominal infections in any of the patients. The neurological status of all of the patients was improved by at least one American Spinal Injury Association grade by the last follow-up. The anterior vertebral body height was an average of 50.77% before surgery, 88.51% after surgery and 87.86% at the last follow up; the sagittal Cobb angle was improved, on average, from 26.15° to 5.39° and was 5.90° at the last follow up. The percentage of spinal stenosis was improved, on average, from 26.07% to 4.93%° and was 6.15% at the last follow up. There were significant differences in the anterior vertebral body height pre- and post-surgery and in the sagittal Cobb angle and the percentage of spinal stenosis (p